The impact of the banking sector crisis upon the Ukrainian investment fund market - Trzebiński, Artur A. (Wpływ sektora bankowego na rynek funduszy inwestycyjnych na Ukrainie, 2017)
This study is an attempt at evaluating the impact of the banking sector crisis of 2014-2016 upon the Ukrainian market of investment funds. The analyses cover a period between 2004 and the 2nd quarter of 2016, to illustrate the trend of changes observed on the market under study. The main focus of research was placed on platforms shared between the banking sector and the investment fund sector, such as the investment of free fund assets in bonds and shares issued by banking institutions or the use of financial instruments targeted to specific investor groups). Based on the findings, it may be concluded that the force of the systemic crisis’ impact upon the market of investment funds was related to the type of investment funds under examination. The effects of the sector’s decline were clearly reflected in the operation of open-end funds and interval funds, as evidenced by sizeable reductions of both their net assets and rates of return. For other types of investment funds, the researchers found no evidence of any impact in this respect
Nauki o Finansach = Financial Sciences, 2017, Nr 2 (31), s. 92-101
Keywords: mutual funds; banking sector; banking sector crisis; fundusze inwestycyjne; sektor bankowy; kryzys sektora bankowego